Root functional traits explain root exudation rate and composition across a range of grassland species - Williams, Alex; Langridge, Holly; Straathof, Angela L.; Muhamadali, Howbeer; Hollywood, Katherine A.; Goodacre, Royston; Vries, Franciska T. (The Journal of ecology, 2022)
Plant root exudation is a crucial means through which plants communicate with soil microbes and influence rhizosphere processes. Exudation can also underlie ecosystem response to changing environmental conditions. Different plant species vary in their root exudate quantity and quality, but our understanding of the plant characteristics that drive these differences is fragmentary. We hypothesised that root exudates would be under phylogenetic control and fit within an exploitative root nutrient uptake strategy, specifically that high rates of root exudation would link to root traits indicative of exploitative growth. We collected root exudates from plants grown in field soil, as well as leachates of the entire plant–soil system, to assess both the quantity and quality of root exudates, and their interaction with the soil metabolome, across 18 common grassland species. We found that exudation varied with plant functional group and that differences were trait dependent. Particularly, root diameter, root tissue density and root nitrogen content explained much of the variation in exudate metabolome, along with plant phylogeny. Specific root exudation rate was highest in forbs and was negatively correlated with root tissue density, a trait indicative of conservative resource‐use strategy, and positively correlated with root diameter, which is associated with microbial collaboration and resource uptake ‘outsourcing’. Synthesis. We provide novel insight into species‐specific differences in root exudates and identify root functional traits that might underlie these differences. Our results show that root exudation fits, although not entirely, within current models of the root economic space, with strong positive relationships to outsourcing traits like high root diameter. Determining the role of root exudates as a key facet of the resource‐outsourcing strategy necessitates further research into the fundamental controls on root exudation quantity and quality, particularly during environmental change. Our study shows that root exudates fit into the root economic spectrum and are associated with resource‐outsourcing traits: exudation rates increase with root diameter, decrease with root tissue density and operate under plant phylogenetic control. Metabolite composition of exudates is species specific, with some phylogenetic association. It is likely that quantity and composition operate together in conjunction with root trait syndromes to inform a rhizosphere microbial function consistent with the growth strategy of the plant. Greater consideration and characterisation of root exudates remain key to fully unravelling plant–microbe relationships and their role in plant environmental adaptation and survival.